ВСЕМИРНЫЙ ДОКЛАД О НАРКОТИКАХ 2010 год - United Nations Office on Drugs; Crime (United Nations, 2010)
In order to prepare the World Drug Report, UNODC relies on Member States to provide data, primarily through the Annual Reports Questionnaire (ARQ). The ARQ was distributed to 192 Member States, and UNODC received 110 replies to the drug abuse section and 114 replies to the illicit supply of drugs section from Member States (and territories). In general, most countries’ ability to provide information on illicit drug supply is significantly better than their ability to provide demand-related data. Despite commendable progress, for example in the area of prevalence estimates, far more remains to be done to provide a solid, reliable basis for trend and policy analysis. The report includes in-depth and cross-sectoral analyses of transnational drug markets (chapter 1) as well as the latest statistical data and trends regarding the world drug situation (chapter 2). This year, the report also discusses the impact of transnational drug trafficking on transit countries (chapter 3).